Single-fraction high-dose-rate brachytherapy using real-time transrectal ultrasound based planning in combination with external beam radiotherapy for prostate cancer: dosimetrics and early clinical results - Lauche, Olivier; Delouya, Guila; Taussky, Daniel; Menard, Cynthia; Béliveau-Nadeau, Dominic; Hervieux, Yannick; Larouche, Renée; Barkati, Maroie (Journal of Contemporary Brachytherapy, 2016)
Purpose : To validate the feasibility of a single-fraction high-dose-rate brachytherapy (HDRBT) boost for prostate cancer using real-time transrectal ultrasound (TRUS) based planning. Material and methods : From August 2012 to September 2015, 126 patients underwent a single-fraction HDRBT boost of 15 Gy using real-time TRUS based planning. External beam radiation therapy (EBRT) (37.5 Gy/15 fractions, 44 Gy/22 fractions, or 45 Gy/25 fractions) was performed before (31%) or after (69%) HDRBT boost. Genito-urinary (GU) and gastro-intestinal (GI) toxicity were assessed 4 and 12 months after the end of combined treatment using the international prostate symptom score scale (IPSS) and the common terminology criteria for adverse events (CTCAE) v3.0. Results : All dose-planning objectives were achieved in 90% of patients. Prostate D 90 ≥ 105% and ≤ 115% was achieved in 99% of patients, prostate V 150 ≤ 40% in 99%, prostate V 200 < 11% in 96%, urethra D 10 < 120% for 99%, urethra V 125 = 0% in 100%, and rectal V 75 < 1 cc in 93% of patients. Median IPSS score was 4 at baseline and did not change at 4 and 12 months after combined treatment. No patients developed ≥ grade 2 GI toxicity. With a median follow-up of 10 months, only two patients experienced biochemical failure. Among patients who didn’t receive ADT, cumulative percentage of patients with PSA ≤ 1 ng/ml at 4 and 18 months was respectively 23% and 66%. Conclusions : Single-fraction HDRBT boost of 15 Gy using real-time TRUS based planning achieves consistently high dosimetry quality. In combination with EBRT, toxicity outcomes appear promising. A longer follow-up is needed to assess long-term outcome and toxicities.